DEVELOPMENT OF AN INTEGRATED E-BOOKLET I-SETS (ISLAMIC, SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) ENVIRONMENTAL CHANGE MATERIAL FOR CLASS X SMA/MA STUDENTS - Nana Roisatulkusna; Nasrul Hakim (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2024)
The use of integrated I-SETS (Islamic, Science, Environment, Technology, and Society) learning media on environmental change aims to train students' creativity. This research aims to analyze the feasibility, student responses and teacher responses to the product being developed, namely the I-SETS integrated e-booklet on environmental change. The research carried out is research and development (R&D), using the ADDIE development model. Data collection techniques used were interviews and questionnaires (validation, teacher and student responses). The test subjects were carried out on one teacher and 11 class XI students of SMA Negeri 1 Kotagajah. Data analysis in this research used qualitative and quantitative data. The research results indicate that the media developed has met the following criteria: (1) material expert validation of 74% with "feasible" criteria; (2) media expert validation of 86% with the criteria "very feasible"; (3) the results of the biology teacher response trial with a percentage of 96% showed that the media developed was "very suitable" for use; and (4) assessment of 11 students' response test to the product developed with a percentage of 88% with the criteria being very suitable for use as a learning resource for class environmental changes to train students' creativity.